Soleil à coudre de Jean d’Amérique - Marjorie Jung (Études Caribéennes)
If the initial gap, the founding erasure can be transcended by a reappropriation of language, can we not then affirm that the dialectical movement, tragedy and creation, opens to a possible poetic revolution? The fulgurating poetic prose of Soleil à coudre thus calls for a new body-text, where the ‘screaming’ allows to extract oneself from tragedy by reappropriating not only the place – a diffracted spatiality which is that of the narrator – and a desire which springs up in signifying islets. The reappropriation of the body-suffering muted in body-desiring thus illustrates a mutation, that of a founding uprising: a poetic revolution. The literature, by drawing the possibility to reach its own desire, becomes act of resistance. Act of resistance in front of a mortiferous reality, it allowsto oppose to ‘the death in the life’, a beauty absolute.